2010
DOI: 10.1103/physrevd.82.066007
|View full text |Cite
|
Sign up to set email alerts
|

Holographic p-wave superconductors from Gauss-Bonnet gravity

Abstract: We study the holographic p-wave superconductors in a five-dimensional Gauss-Bonnet gravity with an SU(2) Yang-Mills gauge field. In the probe approximation, we find that when the Gauss-Bonnet coefficient grows, the condensation of the vector field becomes harder, both the perpendicular and parallel components, with respect to the direction of the condensation, of the anisotropic conductivity decrease. We also study the mass of the quasi-particle excitations, the gap frequency and the DC conductivities of the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 75 publications
8
97
0
Order By: Relevance
“…In the case of Gauss-Bonnet p-wave metal/superconductor phase transitions [61], the curvature corrections also imply the growth of the value of the condensation operator. This fact was also confirmed by the previous studies [62][63][64].…”
Section: Jhep03(2016)215supporting
confidence: 89%
“…In the case of Gauss-Bonnet p-wave metal/superconductor phase transitions [61], the curvature corrections also imply the growth of the value of the condensation operator. This fact was also confirmed by the previous studies [62][63][64].…”
Section: Jhep03(2016)215supporting
confidence: 89%
“…It was found that the critical exponent of the condensation in Gauss-Bonnet gravity is β = 1/2 which is consistent with mean-field theory and previous studies [17]. Other studies on the holographic superconductors in the framework of Gauss-Bonnet-AdS black holes were carried out in [18][19][20][21][22][23][24].…”
Section: Jhep04(2016)058supporting
confidence: 87%
“…It would be interesting if one could consider the Gauss-Bonnet holographic superconductor from PowerMaxwell field away from the probe limit and take the backreaction into account. One may also consider the case in which the Gauss-Bonnet coupling α is negative [46]. These issues are currently under investigation and the results will be reported subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%